2021
DOI: 10.3390/polym13234209
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Cellulose-Based Films Prepared from Used Disposable Paper Cups via an Ionic Liquid

Abstract: Paper cups are widely employed in daily life with many advantages, but most of the used paper cups are incinerated or landfilled, due to the great challenge of separating the thin inner polyethylene (PE) coating, causing the waste of energy and the pollution of our environment. Therefore, recycling and converting the used paper cups into high-value materials is meaningful and important. In this work, transparent cellulose-based films were successfully prepared from the used paper cups via 1-allyl-3-methylimida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Meanwhile, the absorption peak at around 899 cm –1 is weak for the CPs, while it enhanced intensely for the regenerated films. All the above phenomena indicate the changes of hydrogen bonds and the transition of cellulose from I to II phase after regeneration, which is in correspondence with our former results. Additionally, PMIA short fibers demonstrate peaks at approximately 1654, 1608, and 1538 cm –1 , assigned to the vibration of the CO (amide) stretching, aromatic ring stretching, and −NH– bending, which are characteristic peaks for the PMIA structure. , Taking the −NH– bending vibration (1538 cm –1 ) and aromatic ring stretching vibration (1608 cm –1 ) as references, it can be concluded that these two peaks are enhanced obviously with more content of PMIA, indicating the successful and homogeneous incorporation of PMIA into the cellulose matrix, which is important to the property of the cellulose/PMIA composite films.…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, the absorption peak at around 899 cm –1 is weak for the CPs, while it enhanced intensely for the regenerated films. All the above phenomena indicate the changes of hydrogen bonds and the transition of cellulose from I to II phase after regeneration, which is in correspondence with our former results. Additionally, PMIA short fibers demonstrate peaks at approximately 1654, 1608, and 1538 cm –1 , assigned to the vibration of the CO (amide) stretching, aromatic ring stretching, and −NH– bending, which are characteristic peaks for the PMIA structure. , Taking the −NH– bending vibration (1538 cm –1 ) and aromatic ring stretching vibration (1608 cm –1 ) as references, it can be concluded that these two peaks are enhanced obviously with more content of PMIA, indicating the successful and homogeneous incorporation of PMIA into the cellulose matrix, which is important to the property of the cellulose/PMIA composite films.…”
Section: Resultssupporting
confidence: 88%
“…Detailed information of the components and crystalline phase changes of CPs, UDPCs (the PE side and after peeling off the PE coatings), PE film, and cellulose/polyethylene composite films are clarified by the X-ray diffraction patterns in Figure 4 a,b. It is clear that the commercial PE film showed obvious peaks at approximately 2 θ = 9.5°, 14.0°, 16.8°, 21.5°, 23.8°, 28.6°, and 36.2° [ 44 ], which can be used as reference. Generally, the raw materials of cellulose possessed typical cellulose I, which exhibited peaks at approximately 2 θ = 15.1°, 16.8°, 22.8°, and 34.5°, corresponding to (1–10), (110), (200), and (004) crystal planes [ 27 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that mechanical properties are a decisive index for films employed as packaging or wrapping materials, and the degree of polymerization (DP) directly affects the tensile strengths of polymer films [ 32 , 44 ]. As measured by Ubbelodhe viscometry, the DP of cellulose in bamboo-based UDPCs was approximately 304, suggesting that the cellulose/PE composite films possessed a relatively high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, biorefineries and biomass-residue valorization have become more and more popular recently, with the energy shortage and environmental pollution [ 41 , 42 ]. In addition, solid wastes from households, such as waste newspaper [ 34 ], paper cups [ 43 ], old textiles [ 44 ] and corrugated papers [ 45 ], are also attractive alternatives to the high-cost raw materials. It was found that waste newspapers can be transformed into regenerated cellulose films and aerogels to be used as packaging and adsorption materials [ 34 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%